Estimates from Below for Blow Up Time for Two Species Chemotaxis System - Bhuvaneswari, V.; Balachandran, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper deals with the two species chemotaxis system in a bounded domain R3 under different boundary conditions. Explicit lower bounds for blow up time are obtained by using differential inequality technique under suitable assumptions on the data.